Efecto de la termoterapia, dimetilsulfóxido y firocoxib en lesiones crónicas del tendón flexor digital profundo y ligamento interóseo en caballos - Martínez Matamoros, David Fabricio (2023)
Horse tendons and ligaments are injured by overstrain of biomechanical resistance, degeneration or trauma. The objective of this study was to evaluate the effect of thermotherapy, firocoxib and dimethyl sulfoxide on the deep digital flexor tendon (DDFT) and Interosseous Ligament (IL), through lameness evaluation and ultrasound examination. Crossbred polo and show jumping horses (n=20) were used, between 8 and 24 years of age with a history of chronic tendon and ligament injuries. Three treatments were applied for 10 days. Thermotherapy (n=6) applied heat (40°C to 45°C)/20 minutes, and cold using gel bags (0°C)/5 minutes over the posterior region of the metacarpus, every 12 hours. Firocoxib (n=7) was administered 0.1mg/kg/24h (po). DMSO (n= 7), 50 g/12h, was applied topically to the TFDP and LI. The grayscale pixels were measured on the ultrasound images (Mindray DP–50 Vet®) (longitudinal and transverse section) by histogram. At the end of the treatment, in the longitudinal section of the DDFT, horses treated with thermotherapy showed an increase in the number of pixels and had a greater number of pixels compared to DMSO. On the other hand, in the cross-section of the Interosseous Ligament, horses treated with firocoxib had an increase in the number of pixels, also, compared to the DMSO treatment. Factors such as the anatomical region studied, the work performed by the horse and age influenced the number of pixels in both ultrasound sections of the DDFT and LI. Before applying the treatments, 25% of the horses were lame and had sensitivity, after treatment, it decreased to 10%. In the correlation, it was observed that as the maximum value of DDFT pixels is reduced and the average and minimum pixels of the LI increase, claudication and sensitivity decrease, therefore in these alterations it was possible to find an improvement